KRAS Mutations in Squamous Cell Carcinomas of the Lung - Acker, Fabian; Stratmann, Jan; Aspacher, Lukas; Nguyen, Ngoc Thien Thu; Wagner, Sebastian; Serve, Hubert; Wild, Peter J.; Sebastian, Martin (Frontiers in Oncology, 2021)
KRAS is one of the most commonly mutated oncogenes in cancer, enabling tumor proliferation and maintenance. After various approaches to target KRAS have failed over the past decades, the first specific inhibitor of the p.G12C mutation of KRAS was recently approved by the FDA after showing promising results in adenocarcinomas of the lung and other solid tumors. Lung cancer, the most common cancer worldwide, is a promising use case for these new therapies, as adenocarcinomas in particular frequently harbor KRAS mutations. However, in squamous cell carcinoma (SCC) of the lung, KRAS mutations are rare and their impact on clinical outcome is poorly understood. In this review, we discuss the current knowledge on the prevalence and prognostic and predictive significance of KRAS mutations in the context of SCC.